2007
DOI: 10.1007/s11708-007-0054-2
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of heavy metals during municipal solid waste incineration on a laboratory fluid bed furnace

Abstract: The content of heavy metals in the main physical compositions of municipal solid waste (MSW) is analyzed. The effects of temperature, chlorine and water on the partitioning of heavy metals are studied using a laboratory fluidized-bed (FB) furnace with simulated MSW com position. The experimental results show that temperature and chloride content in the feed have significant influence on the volatility of heavy metals, especially those of lower boiling point such as Hg, Cd and Zn. The influence of water is slig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…According to Figure b, stabilized rates of HMs in slag decreased with increasing amount of NaCl during the process of calcination. The reason was that heavy-metal chlorides have a higher vapor pressure, and the participation of Cl in thermal treatment of sludge delays the condensation of metal compounds, thereby exacerbating volatilization of HMs. , From Figure b, it can also see that the trends of decrease of Zn and Pb were more obvious than those of As and Cd; this was because that the gaseous HCl was produced by an intermediate mechanism in the removal of HMs (WO) by an inorganic chlorinating agent (MClx), which was different from the removal effect of Cl 2 on HMs. HCl was more favorable for the removal of Zn and Pb, therefore causing a large amount of volatilizing of Zn and Pb.…”
Section: Resultsmentioning
confidence: 97%
“…According to Figure b, stabilized rates of HMs in slag decreased with increasing amount of NaCl during the process of calcination. The reason was that heavy-metal chlorides have a higher vapor pressure, and the participation of Cl in thermal treatment of sludge delays the condensation of metal compounds, thereby exacerbating volatilization of HMs. , From Figure b, it can also see that the trends of decrease of Zn and Pb were more obvious than those of As and Cd; this was because that the gaseous HCl was produced by an intermediate mechanism in the removal of HMs (WO) by an inorganic chlorinating agent (MClx), which was different from the removal effect of Cl 2 on HMs. HCl was more favorable for the removal of Zn and Pb, therefore causing a large amount of volatilizing of Zn and Pb.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, fuelblend chlorine and sulfur content and Cl/S ratio are key parameters for heavy metal volatilization. Research by Li et al 18 indicated that higher chloride content in municipal solid waste had a noticeable effect on heavy metal (e.g., Hg, Cd, and Zn) volatilization in a fluidized bed furnace. A study by Liu et al 19 showed that the addition of sulfur compounds reduces Cd volatilization by forming CdS and polymetallic sulfides that stabilize Cd in bottom ash during the sludge incineration process.…”
Section: Introductionmentioning
confidence: 99%